-1-6(-b-4)=8b+7

Simple and best practice solution for -1-6(-b-4)=8b+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1-6(-b-4)=8b+7 equation:


Simplifying
-1 + -6(-1b + -4) = 8b + 7

Reorder the terms:
-1 + -6(-4 + -1b) = 8b + 7
-1 + (-4 * -6 + -1b * -6) = 8b + 7
-1 + (24 + 6b) = 8b + 7

Combine like terms: -1 + 24 = 23
23 + 6b = 8b + 7

Reorder the terms:
23 + 6b = 7 + 8b

Solving
23 + 6b = 7 + 8b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-8b' to each side of the equation.
23 + 6b + -8b = 7 + 8b + -8b

Combine like terms: 6b + -8b = -2b
23 + -2b = 7 + 8b + -8b

Combine like terms: 8b + -8b = 0
23 + -2b = 7 + 0
23 + -2b = 7

Add '-23' to each side of the equation.
23 + -23 + -2b = 7 + -23

Combine like terms: 23 + -23 = 0
0 + -2b = 7 + -23
-2b = 7 + -23

Combine like terms: 7 + -23 = -16
-2b = -16

Divide each side by '-2'.
b = 8

Simplifying
b = 8

See similar equations:

| h+12-5h=28 | | (x)-7=50 | | 3+2n+3n=10+6n | | (4/7y)^2 | | 4*0=5*0 | | 5/3p=-40 | | 9-(-3V-9)=54 | | 45=10x+15 | | 2(y+3)=3y+7 | | n-7=3-4n | | X=10-1/3y | | 5(3+7x)=-2x+15 | | 69(2x+4)=180 | | 10z-4+(k+11)=8k-7 | | T+12.7=-7.4 | | 15g-14g=16 | | 14x+4y+20+16x-5y-18= | | 9-(3V-9)=54 | | 142(2x+4)=180 | | -175=-7(5x-30) | | V-1=1+2v | | 7.61=2(3.14r) | | w/102=102 | | (x)=12 | | n+(n+2)=97 | | 32(2x+4)=180 | | 12-4x=-18+4x | | x^2+12x=c | | -0.75x+5=0.25x-3 | | 13+4p=1+6p | | 3x/5=-2/35 | | 5x+y+4x+2y=90 |

Equations solver categories